Anterior cerebral artery infarcts; Two years follow-up study - Hanoğlu, Lütfü; Khanmammadov, Elmir; Demirci, Sema; Altın, Ümmühan; Kırbaş, Dursun; Hanoğlu, Taha; Yuluğ, Burak (Literatura Medical, 2018)
Objectives - Anterior cerebral infarct (ACA) infarcts are reported very rare that is due to the compensatory collateral circulation provided by the anterior communicating artery. There are very few studies reporting the long-term follow-up results of ACA infarcts regarding their aetiology, clinical features and prognosis. Most studies reported in the literature vary between several months to one year. Patients and methods - A total of 27 patients with ACA infarcts were registered (14 women and 13 men). The mean age of the patients was 68.5 (age range: 45-89 years). Results- Bilateral ACA infarcts were reported in four patients (14.8%), right ACA infarct in 11 (40%) patients and left ACA infarct in 12 patients (44%). During the initial examination 15 patients (55.5%) were found to have apathy, 13 patients (48%) had incontinence, nine patients (33.3%) had primitive reflexes, 11 patients (40.7%) had aphasia, while six patients (22.2%) were found to suffer from neglect. At the end of one-year follow-up, five patients (22.7%) were reported to have apathy, 6 patients (27.2%) had incontinence, one patient (4.5%) had primitive reflexes, while one patient (4.5%) was found to have permanent aphasia, and no patients was found to suffer from neglect. Conclusion - Here we present our clinical data regarding the aetiology, specific clinical characteristics (including the speech disorders) and prognosis of 27 patients with ACA infarcts during a relatively longer follow-up period (3 months - 30 months) in compared to previous literature. We show that there are differences in the etiological factors of ACA infarcts between the Asian and European communities. Regarding speech disorders which are frequently reported during ACA infarcts, our study results are in agreement with other studies suggesting that this clinical picture is more than a real aphasia and associated with general hypokinesia and reduction in psychomotor activity.
WOS: 000447959300005
PubMed ID: 30335265
Keywords: Anterior Cerebral Artery Infarct; Neurocognitive Dysfunction; Motor Dysfunction; Rankin Scores; TOAST Classification